2006
DOI: 10.1111/j.1468-1331.2006.01249.x
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency of Parkin, Tyrosine Hydroxylase, and GTP Cyclohydrolase I gene mutations in a Danish population of early‐onset Parkinson's Disease

Abstract: Autosomal recessive Parkinson's disease (PD) with early-onset may be caused by mutations in the parkin gene (PARK2). We have ascertained 87 Danish patients with an early-onset form of PD (age at onset < or =40 years, or < or =50 years if family history is positive) in a multicenter study in order to determine the frequency of PARK2 mutations. Analysis of the GTP cyclohydrolase I gene (GCH1) and the tyrosine hydroxylase gene (TH), mutated in dopa-responsive dystonia and juvenile PD, have also been included. Ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 38 publications
1
22
1
Order By: Relevance
“…The patient also has a heterozygous duplication of exon 11 in the parkin gene. An additive effect of the two mutations may account for developing PD at an early age-at-onset in this patient (Hertz et al, 2006). 3) Animal studies have shown that TH enzyme activity decreases by age.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The patient also has a heterozygous duplication of exon 11 in the parkin gene. An additive effect of the two mutations may account for developing PD at an early age-at-onset in this patient (Hertz et al, 2006). 3) Animal studies have shown that TH enzyme activity decreases by age.…”
Section: Discussionmentioning
confidence: 94%
“…The rate limiting step in dopamine biosynthesis is catalyzed by the enzyme encoded by the tyrosine hydroxylase ( TH ; MIM# 191290 ) gene (Haavik and Toska., 1998). Consistent with its essential role in dopamine homeostasis, homozygous missense mutations in TH have been associated with dopamine-related phenotypes, such as Segawa's syndrome, L-DOPA responsive infantile parkinsonism, and L-DOPA responsive dystonia (DRD) (Furukawa et al, 2001; Hertz et al, 2006). However, it is not clear whether a single allele mutation in TH would modify an individual's susceptibility to PD.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies investigating the contribution of rare coding GCH1 variants in small cohorts of cases with Parkinson’s disease have reported negative results although these were insufficiently powered to draw conclusions (Bandmann et al , 1996 a ; Hertz et al , 2006; Cobb et al , 2009). An as-yet unpublished meta-analysis of existing genome-wide association study data has, however, identified GCH1 as a common low-risk locus (Singleton, personal communication), consistent with the hypothesis of a causal role for GCH1 in Parkinson’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, only six PD patients (4%) possessed PRKN mutation (Table 2), which is lower than that reported in several comparable studies, which report PRKN mutations to be present in between 10.4 and 18.0% of early-onset cases. [18][19][20][21] Five missense mutations identified in our patients are located in the important functional domain of Parkin, that is, one in UBL, another in UPD, two in RING1, whereas other in IBR region-thus likely to be involved in the impairment of Parkin Interestingly, none of the 300 chromosomes harbored the variants suggesting the potential role of these mutations, if any, in PD, require to be evaluated by functional analysis. The novel mutation (ex 5, GTT4ATT) is predicted to be 'possibly damaging' (PolyPhen, http://coot.embl.de/PolyPhen/; SNPs3D, Mutation taster) and the amino acid in this position is highly conserved through Macaca mulatta, Pan paniscus, Callithrix jacchus, Bos mutus, Sus scrofa, Rattus norvegicus and Canis familiaris.…”
Section: Discussionmentioning
confidence: 92%